Fiscal Discipline and Stability under Currency Board Systems - Oliver Grimm (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
In economic discussions, currency board systems are frequently described as arrangements with self-binding character to the monetary authorities by their strict rules and establishments by law. Hard pegs and especially currency boards are often seen as remedies to overcome economic and financial turmoils and to return to low inflation. A sustainable debt level closely linked to a disciplined fiscal policy is, however, a premise for medium-term success. We show in a two-period model that the choice of a currency board can increase fiscal discipline compared to a standard peg regime. We derive, furthermore, the conditions for a currency boards to gain a stability advantage compared to a common peg system.
Keywords: E52; E58; E62; F33; 330; currency board; fixed exchange rate; commitment; inflation bias; fiscal discipline; public debt; time-inconsistency problem; Currency-Board-System; Fester Wechselkurs; Finanzpolitik; Öffentliche Schulden; Inflation; Systematischer Fehler; Zeitkonsistenz; Theorie